Student Dropout and Institutional Preventive Measures in Tribhuvan University’s One-Year ODL Programme - Adhikari, Min Raj (Teacher Half-Yearly Journal, 2025)
The Open and Distance Learning (ODL) Programme offers opportunities for learners to enhance their academic qualifications without leaving their jobs or professions. In 2019, Tribhuvan University launched a one-year ODL Programme in M.Ed Science and PGD in Social Studies Education at Mahendra Ratna Campus, Kathmandu. This study aims to investigate the reasons for student dropout and propose prevention strategies, specifically focusing on the one-year ODL Programme of Tribhuvan University. Data was collected through a self-administered questionnaire using a Google Survey form, targeting all 103 students enrolled in the 2019 ODL Programme. A total of 45 students participated in the Google survey form. Frequency table and cross tables were employed to analyze data using SPSS 20.Out of 45 respondents, two-fifths dropped out at the master's level and two-thirds at the PGD level. Major causes were institutional (58%) like overloaded assignments (32%) and centralized exams (26%), and non-institutional (42%) like poor internet access and family issues (10.5% each), and work-study balance (21%). Institutional dropout prevention measures, including scholarships, support, altered schedules, tutoring, and counseling, were inadequate. Urgent changes needed include modifying assignment patterns, providing flexible deadlines, and establishing an online or decentralized exam system. Effective measures are crucial to prevent dropouts and keep students enrolled.